O valor-trabalho: a substância do valor na economia política clássica - Guilherme Habib Santos Curi (2016)
This works presents, in the light of Karl Marx, the path followed by classical political economy toward the substance of value. The first steps of this science coincide with the rise of a new social class: the bourgeoisie. At the end of the seventeenth century, the bourgeoisie took political power in England. During this period, a brilliant thinker, William Petty, conceived for the first time the concept of value in line with the newly emerged mode of production. Petty noted that value was as much a social product, employment, as a natural product, land. Decades later, a young American, Benjamin Franklin was responsible for reducing value to a single determinant: the amount of work. To that extent, Franklin must be recognized as one of the main responsibles for developing the theory of value toward its truth. He broke with the pettyan tradition and recognized work as the sole foundation of value. Physiocracy, here represented by François Quesnay, highlighted the materiality of all mercantile wealth and illuminated the expansionary nature characteristic of a value producing society. Classical political economy reached its maturity with Adam Smith, when he tried to deal systematically with the totality of the content of economic science itself. Smith, however, could not handle all the issues of his object of study and was therefore unable to build a fully consistent system. Ricardo is the last author of our narrative. He was responsible for taking the theory of labor contained in Franklinand Smith to its ultimate consequences and, by doing so, having reached the [proper environment] for the production of value. Ricardo blazed the sphere of production, where the substance of value presents no disguise. He was, to that extent, responsible for presenting the work as a basis of the capitalist mode of production, by making work, according to its quality, the substance of value. Consequently he imposed the limit of political economy -- by sheding light on the contradictory essence of bourgeois society, he determined the end of the disinterested economic research and announced the era of apology.